2020
DOI: 10.1063/1.5142877
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of entropy generation for the non-similar three-dimensional bioconvection flow of nanofluids

Abstract: This research work presents the entropy analysis of the three-dimensional bioconvection flow of nanofluid over a linearly moving plate in the presence of magnetic effects. Nanoparticles and microorganisms have been considered in the fluid, with the magnetic field acting in the transverse direction to the plate. The viscous dissipation term is also considered in the energy equation. The partial differential equations (PDEs) of the boundary layer region of this problem are transformed with suitable non-similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Khan et al [22] evaluated the EG in nanofluid flow through porous medium comprising microorganisms and nanoparticles. Some important studies on EG have been conducted in [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [22] evaluated the EG in nanofluid flow through porous medium comprising microorganisms and nanoparticles. Some important studies on EG have been conducted in [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Hayat [35] also solved non-similarity flow of nanofluid and obtained a series solution. Farooq et al [36] investigated aspects of entropy for non-similar three-dimensional flow of nanofluid in presence of magnetic effect. Shukla et al [37] found a non-similar solution for non-Newtonian fluid by using a local non-similar method.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatti et al 34 investigated the entropy generation past a moving surface with thermal radiation and chemical reaction using successive linearization method and chebyshev spectral collocation method for the reduced resulting non-linear coupled ordinary differential equations. Farooq et al 35 presented the entropy analysis of three-dimensional bioconvection flow of nanofluid past a linearly moving plate in the presence of magnetic field and microorganisms by applying the BVP4c MATLAB algorithm. Mondal et al 36 discussed the entropy generation and provided the dual solutions with the spectral quasiliearization method for the magnetohydrodynamic three-dimensional convective flow and heat transfer in a nanofluid.…”
Section: Introductionmentioning
confidence: 99%